Agricultural Extension Performance Reviewed From the Perspective of Competence, Motivation and Work Environment - Nataliningsih,; Suseno, Gijanto Purbo; Sugiyanto,; Genta, Franklin Kharisma (International Journal of Psychosocial Rehabilitation, 2020)
Indonesia is an agricultural country with agriculture as a source of income, therefore agriculture in Indonesia should be developed. To support agricultural progress, the role of agricultural extension is very important. The number of agricultural extension workers in the district of Bandung is 60 people, the number of which has not supported the progress of agriculture in Bandung district. Therefore it needs to be researched perspectives that support the performance of agricultural extension workers. This research uses a quantitative approach with 3 independent variables, namely competence, motivation and environment of extension worker and 1 dependent variable that is extension worker. Data analysis using Path Way method of analysis The results showed that the competence of agricultural extension in Bandung district was high with 4,612.00 value, motivation perspective value 2,722.00 with high category, work environment perspective with 2,088.00 value with high category and performance perspective with total value 4,067,00 with category high. Perspective competence and motivation have a positive effect on extension worker performance, while the work environment perspective does not affect farmer extension performance. The mathematical model obtained by using Path Way analysis is Y = 0.1771 X1 + 0,2168 X2 - 0,3661 X3 + 0,0977 (ε). The suggestion given is the need for research needs analysis of extension workers in order to improve extension performance.